Self and identity : personal, social, and symbolic - Kashima, Yoshihisa, 1957-; Foddy, Margaret; Platow, Michael (Lawrence Erlbaum Associates, 2002)
This edited volume outlines the latest meta-theoretical and theoretical contexts of self-research. Self and Identity examines theoretical accounts of human experience within the contemporary socio-cultural milieu and attempts to answer the question of what it means to be human.